Cartel Fines and Their Judicial Review by the Court of Justice of the European Union - Vesikallio, Kai (Helsinki Law Review, 2016)
Under its 2006 Guidelines on the method of setting fines the European Commission has increased the level of fines it imposes on undertakings and associations of undertakings that have participated in a cartel infringement. These fines are, however, subject to judicial review by the Court of Justice of the European Union, which has unlimited jurisdiction with regard to the fines. Formerly, the court has been relatively generous in terms of reducing the fines; most of the cartel fine appeals have resulted in a reduced fine either in the General Court or in the Court of Justice. Now, due to the significant increase in the level of fines, it is interesting to find out whether there have been any notable changes in the courts’ assessment of the fines. In this paper recent case law of both the General Court and the Court of Justice is analyzed. Based on this analysis, it is among other things argued that, after introduction of the Guidelines, fewer appeals than before result in a reduced fine. Moreover, it is argued that there have been noteworthy changes in the grounds of fine reductions.